Scleralfixatedintra-ocularlens : A case report - Pai, Vijay; Shetty, Jayaram; Amin, Hrishikesh; Shetty, Samatha P. (Journal of Health and Allied Sciences NU, 2015)
In the surgical management of aphakia in cases with deficient posterior capsule1, we have described this particular technique which is cost effective and technically less challenging at the same time with satisfactory results.
Keywords: Scleral fixated IOL; SFIOL; Intraocular lens; Aphakia; Secondary IOL